People's Republic of China-Hong Kong Special Administrative Region : Financial Sector Assessment Program-Technical Note-Systemic Risk Oversight and Macroprudential Policies. (IMF Staff Country Reports; Country Report ;, 2021)
The institutional framework for Macroprudential Policies (MaPP) in the Hong Kong Special Administrative Region (the Hong Kong SAR) is well established. According to the Basic Law, the Government of the Hong Kong SAR shall on its own formulate monetary and financial policies. The Financial Secretary (FS) and the Secretary for Financial Services and the Treasury (SFST) are responsible for policies for maintaining the stability and integrity of the financial system of the Hong Kong SAR. The Hong Kong SAR has a sector-based regulatory structure and the responsibilities and tools for safeguarding financial stability are spread across the Financial Services and the Treasury Bureau (FSTB) and three regulators (namely, the Hong Kong Monetary Authority (HKMA), Securities and Futures Commission (SFC) and Insurance Authority (IA)). There are good and well-structured interagency coordination and consultation mechanisms, through the Council of Financial Regulators (CFR) and the Financial Stability Committee (FSC), chaired by the FS and the SFST, respectively. Broad coordination between the CFR and government agencies on taxation and housing supply-side policies has also worked well. MaPP and risk assessment are communicated to the public openly and frequently through speeches, press releases and regular publications, including the Half-Yearly Monetary and Financial Stability Report of the HKMA and the Half-yearly Review Report of the Global and Local Securities Markets of the SFC.